IMPROVING STUDENTS’ VOCABULARY BY USING WORD GAME APPLICATION - Hertila Umbola; Mister G. Maru; Paula Hampp (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This study aims to prove whether the Word Game Application which is Wordscapes can help students to improve their vocabulary or not. In this study, the researcher employed the quantitative research method. The subject of this study is class X J at SMA N 1 Kotamobagu which consists of 30 students (13 are boys and 17 are girls with an average age of 15-17 years old). Data were collected using pre-test and post-test design in the form of matching tests. The result of this study proves that the mean scores of the post-test are higher than the mean scores of the pre-test. The mean scores of the pre-test is 63.16 and the mean scores of post-test is 85.83. Based on the results obtained, it can be concluded that the Word Game Application which is Wordscapes can help students to improve their vocabulary mastery and make students more enthusiastic in learning.